Sosialisasi Dan Edukasi PemanfaatanVitamin Kepada Siswa Siswi di SD Negeri 02 Jetak Kidul - sutomo, tsanyandary; Haqiqi, Izzatul; Putra, Fikri Farrasyah; Putri, Mega Widya (Jurnal Muhammadiyah untuk Olahraga Indonesia, 2024)
Since 2022, there has been an outbreak of the Covid-19 pandemic in Indonesia. Since then, discipline is needed in implementing health protocols and maintaining health to improve the body's immune system so that it can avoid bacteria and viruses by adopting healthy living behaviors, one example of which is consuming vitamins. This community service aims to provide knowledge and information in the form of socialization and health education to participants about the use of vitamins in children. This activity was carried out at SD Negeri 02 Jetak Kidul, Kec. Wonopringgo, Kab. Pekalongan, Jawa Tengah. The method used in this service is an approach method in the form of lectures, discussions and questions and answers regarding the use of children's vitamins.